Hypoxemia following generalized convulsive seizures: Risk factors and effect of oxygen therapy. (15th January 2019) - Rheims, Sylvain; Alvarez, Blanca Mercedes; Alexandre, Veriano; Curot, Jonathan; Maillard, Louis; Bartolomei, Fabrice; Derambure, Philippe; Hirsch, Edouard; Michel, Véronique; Chassoux, Francine; Tourniaire, Didier; Crespel, Arielle; et al.
Abstract : Objective: To analyze the factors that determine the occurrence or severity of postictal hypoxemia in the immediate aftermath of a generalized convulsive seizure (GCS). Methods: We reviewed the video-EEG recordings of 1, 006 patients with drug-resistant focal epilepsy included in the REPO2 MSE study to identify those with ≥1 GCS and pulse oximetry (SpO2 ) measurement. Factors determining recovery of SpO2 ≥ 90% were investigated using Cox proportional hazards models. Association between SpO2 nadir and person- or seizure-specific variables was analyzed after correction for individual effects and the varying number of seizures. Results: A total of 107 GCS in 73 patients were analyzed. A transient hypoxemia was observed in 92 GCS (86%). Rate of GCS with SpO2 <70% dropped from 40% to 21% when oxygen was administered early ( p = 0.046). Early recovery of SpO2 ≥90% was associated with early administration of oxygen ( p = 0.004), absence of postictal generalized EEG suppression (PGES) ( p = 0.014), and extratemporal lobe epilepsy ( p = 0.001). Lack of early administration of O2 ( p = 0.003), occurrence of PGES ( p = 0.018), and occurrence of ictal hypoxemia during the focal phase ( p = 0.022) were associated with lower SpO2 nadir. Conclusion: Postictal hypoxemia was observed in the immediate aftermath of nearly all GCS but administration of oxygen had a strong preventive effect. Severity of postictal hypoxemia was greater in temporal lobe epilepsy and when hypoxemia was already observed before the onset of secondary GCS.